2014
DOI: 10.1371/journal.pone.0106592
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Specificity of the Blood–CSF Barrier for Albumin Transfer across the Choroid Plexus Epithelium

Abstract: To maintain the precise internal milieu of the mammalian central nervous system, well-controlled transfer of molecules from periphery into brain is required. Recently the soluble and cell-surface albumin-binding glycoprotein SPARC (secreted protein acidic and rich in cysteine) has been implicated in albumin transport into developing brain, however the exact mechanism remains unknown. We postulate that SPARC is a docking site for albumin, mediating its uptake and transfer by choroid plexus epithelial cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…Immunolocalization of SPARC in apical vesicles of mouse choroid plexus epithelial cells and immunolabeling of albumin in multivesicular bodies in sheep choroid plexuses are both consistent with that hypothesis [138]. It would also be consistent with the presence of albumin/SPARC complexes (detected by the in situ proximity ligation assay) in the ependymal and subependymal layer [139]. …”
Section: Routes Of Drug Delivery Into the Csf Through The Choroid Plexussupporting
confidence: 68%
“…Immunolocalization of SPARC in apical vesicles of mouse choroid plexus epithelial cells and immunolabeling of albumin in multivesicular bodies in sheep choroid plexuses are both consistent with that hypothesis [138]. It would also be consistent with the presence of albumin/SPARC complexes (detected by the in situ proximity ligation assay) in the ependymal and subependymal layer [139]. …”
Section: Routes Of Drug Delivery Into the Csf Through The Choroid Plexussupporting
confidence: 68%
“…However, Neesse et al showed that tissue and plasma concentrations of nab -paclitaxel were comparable with those of mouse albumin bound paclitaxel (20). Liddelow et al also showed that human albumin bound mouse SPARC (36). …”
Section: Discussionmentioning
confidence: 99%
“…Radiolabeled albumin may also be processed in the body during the experimental period through normal albumin turnover resulting in liberation of radiolabeled amino acids and reincorporation into proteins that are subsequently absorbed into the brain parenchyma [13]. Finally, access of albumin to the CSF has been reported, which may result in some appearance of the radiolabel in the brain [25]. Although any or all of these mechanisms may be responsible for the background albumin levels in control animals, the comparison with CCI-treated animals is compelling and future studies with small molecule drugs may help to discriminate between these effects.…”
Section: Discussionmentioning
confidence: 99%